Initial and long-term antithrombotic therapy after left atrial appendage closure with the WATCHMAN. (25th November 2020) - Ledwoch, J; Sievert, K; Boersma, L; Bergmann, M; Ince, H; Kische, S; Pokushalov, E; Schmitz, T; Schmidt, B; Gori, T; Meincke, F; Protopopov, A; et al.
Abstract: Background: Evidence regarding post-procedural antithrombotic regimes other than used in randomized trials assessing percutaneous left atrial appendage (LAA) closure is limited. Purpose: The present work aimed to compare different antithrombotic strategies applied in the real-world EWOLUTION study. Methods: A total of 998 patients with successful WATCHMAN implantation at 47 centers were available for the present analysis. The composite ischemic endpoint of stroke, TIA, systemic embolism and device thrombus as well as the bleeding endpoint defined as at least major bleeding according to BARC were assessed during an initial period (from implant until first medication change) and long-term period (from first change until up to 2 years). Results: The antithrombotic medication chosen in the initial phase was dual antiplatelet therapy (DAPT) in 60%, oral anticoagulation (OAC) in 27%, single antiplatelet therapy (SAPT) in 7% and no medication in 6%. In the long-term phase SAPT was used in 65%, DAPT in 23%, no therapy in 8% and OAC in 4%. No significant differences were found between the groups regarding the ischemic endpoint both in the initial period (Kaplan-Meier estimated rate 2.9% for DAPT vs. 4.3% for OAC vs. 3.9% for SAPT or no therapy; p=0.97) and in the second period (4.2% for SAPT vs. 1.8% for DAPT vs. 3.5% for no therapy; p=0.36). With respect to bleeding events the only difference was found in the initial phase with a higher incidence in patients under SAPT or no therapy (1.0% for DAPT vs. 0.8% for OAC vs. 7.4% for SAPT or no therapy; p=0.01). No differences in bleeding complications were observed during the second period (2.6% for SAPT vs. 2.9% for DAPT vs. 2.2% for no therapy; p=0.88). Conclusions: Tailored antithrombotic treatment using even very reduced strategies such as SAPT or no therapy showed no significant differences regarding ischemic complications after LAA closure. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Boston Scientific